2010
DOI: 10.1029/2010gl042737
|View full text |Cite
|
Sign up to set email alerts
|

A simplified description of the evolution of organic aerosol composition in the atmosphere

Abstract: Organic aerosol (OA) in the atmosphere consists of a multitude of organic species which are either directly emitted or the products of a variety of chemical reactions. This complexity challenges our ability to explicitly characterize the chemical composition of these particles. We find that the bulk composition of OA from a variety of environments (laboratory and field) occupies a narrow range in the space of a Van Krevelen diagram (H:C versus O:C), characterized by a slope of ∼−1. The data show that atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
599
4
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 524 publications
(671 citation statements)
references
References 31 publications
66
599
4
2
Order By: Relevance
“…On the other hand, if the oxidation reaction involves fragmentation-the cleavage of C-C bonds-and subsequent loss of carbon to the gas phase, then the resulting slope can take on a range of different values, depending on the chemical characteristics of the volatilized fragment. While previous studies have observed that measured ratios and trajectories of reduced and lightly oxidized organic aerosol follow a line with a slope of -1 19 , the data presented here have slopes ranging from -0.6 to -0.3 (Table 1). This tendency of 9 more highly oxidized systems to acquire oxygen with a smaller net loss of hydrogen is consistent with recent studies of the aging of oxidized organic aerosol 20 .…”
Section: Elemental Analysiscontrasting
confidence: 65%
See 3 more Smart Citations
“…On the other hand, if the oxidation reaction involves fragmentation-the cleavage of C-C bonds-and subsequent loss of carbon to the gas phase, then the resulting slope can take on a range of different values, depending on the chemical characteristics of the volatilized fragment. While previous studies have observed that measured ratios and trajectories of reduced and lightly oxidized organic aerosol follow a line with a slope of -1 19 , the data presented here have slopes ranging from -0.6 to -0.3 (Table 1). This tendency of 9 more highly oxidized systems to acquire oxygen with a smaller net loss of hydrogen is consistent with recent studies of the aging of oxidized organic aerosol 20 .…”
Section: Elemental Analysiscontrasting
confidence: 65%
“…Atmospheric oxidation of the most oxidized organic aerosol is therefore unlikely to be a significant sink of aerosol mass, though it is still capable of transforming the chemical composition-and therefore key properties such as hygroscopicity 1,29,30 oxygen-to-carbon (O/C) at all points during the oxidation of the four systems in this study. The solid black line represents observations of ambient aerosol at moderate levels of oxidation 19 . The dashed black line represents measurements of ambient OOA at higher oxidation levels 20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation of VOCs is thought to be a key source of organic acids with recent studies providing new insight into their formation pathways and properties [Paulot et al, 2011;Sommariva et al, 2011;Andrews et al, 2012;Millet et al, 2015;Yuan et al, 2015]. Recent studies indicate organic acids can be a large fraction of SOA at locations highly influenced by biogenic emissions [Vogel et al, 2013], and it has been hypothesized that their fractional contribution to OA increases with increasing photochemical age [Heald et al, 2010;Levin et al, 2014]. However, quantitative determination of the fraction of submicron OA that is composed of organic acids is still limited despite indications that they can be a substantial fraction of OA [Russell et al, 2011].…”
Section: Introductionmentioning
confidence: 99%